IMF Staff Papers, Volume 48, No. 3 - Flood, Robert (IMF Staff Papers; IMF Staff Papers ;, 2002)
This paper analyzes the financial implications of the 1956 crisis of nationalization of the Suez Canal by Egypt. It examines the regional distribution of public employment in Italy. The paper quantifies the impact of changes in the U.S. monetary policy on sovereign bond spreads in emerging market countries. Specifically, the paper explores empirically how country risk, as proxied by sovereign bond spreads, is influenced by U.S. monetary policy, country-specific fundamentals, and conditions in global capital markets. Modeling the IMF's statistical discrepancy in the global current account is also discussed.